Re-examining causes of surgical site infections following elective surgery in the era of asepsis. Issue 3 (March 2020) - Alverdy, John C; Hyman, Neil; Gilbert, Jack
Summary: The currently accepted assumption that most surgical site infections (SSIs) occurring after elective surgery under standard methods of antisepsis are due to an intraoperative contamination event, remains unproven. We examined the available evidence in which microbial cultures of surgical wounds were taken at the conclusion of an operation and determined that such studies provide more evidence to refute that an SSI is due to intraoperative contamination than support it. We propose that alternative mechanisms of SSI development should be considered, such as when a sterile postoperative wound becomes infected by a pathogen originating from a site remote from the operative wound—eg, from the gums or intestinal tract (ie, the Trojan Horse mechanism). We offer a path forward to reduce SSI rates after elective surgery that includes undertaking genomic-based microbial tracking from the built environment (ie, the operating room and hospital bed), to the patient's own microbiome, and then to the surgical site. Finally, we posit that only by generating this dynamic microbial map can the true pathogenesis of SSIs be understood enough to inform novel preventive strategies against infection following elective surgery in the current era of asepsis.